Glycine receptor mutants of the mouse: what are possible routes of inhibitory compensation? - Schäfer, Natascha; Vogel, Nicolas; Villmann, Carmen (Frontiers in Molecular Neuroscience, 2012)
Defects in glycinergic inhibition result in a complex neuromotor disorder in humans known as hyperekplexia (OMIM 149400) with similar phenotypes in rodents characterized by an exaggerated startle reflex and hypertonia. Analogous to genetic defects in humans single point mutations, microdeletions, or insertions in the Glra1 gene but also in the Glrb gene underlie the pathology in mice. The mutations either localized in the ? (spasmodic, oscillator, cincinnati, Nmf11) or the ? (spastic) subunit of the glycine receptor (GlyR) are much less tolerated in mice than in humans, leaving the question for the existence of different regulatory elements of the pathomechanisms in humans and rodents. In addition to the spontaneous mutations, new insights into understanding of the regulatory pathways in hyperekplexia or glycine encephalopathy arose from the constantly increasing number of knock-out as well as knock-in mutants of GlyRs. Over the last five years, various efforts using in vivo whole cell recordings provided a detailed analysis of the kinetic parameters underlying glycinergic dysfunction. Presynaptic compensation as well as postsynaptic compensatory mechanisms in these mice by other GlyR subunits or GABA(A) receptors, and the role of extra-synaptic GlyRs is still a matter of debate. A recent study on the mouse mutant oscillator displayed a novel aspect for compensation of functionality by complementation of receptor domains that fold independently. This review focuses on defects in glycinergic neurotransmission in mice discussed with the background of human hyperekplexia en route to strategies of compensation.
EVALuna2:4692